Assessing the digital literacy competence of pre-service English teacher in Indonesia and Thailand - Yuvita Yuvita; Ahmad Husain; Anin Eka Sulistyawati; Noeris Meiristiani; Eva Fatimah; Sakina Sunmud (Journal of Education and Learning (EduLearn), 2023)
The notion of digital literacy has become the trend in any field, including this research. This research aimed to find the level of digital literacy and adequate and inadequate domains in each pre-service teachers of English education digital literacy group. Quantitative research with digital competence framework or DCF then adjusted and validated through the expert judgment by Aiken V as the main questionnaire occurred to measure the level of digital literacy. Indonesia and Thailand pre-service teacher in various universities participated in this research. The research found that: i) The most level of digital literacy whether in Indonesia and Thailand, the pre-service teacher has an intermediate level followed by basic and advanced and ii) The researcher claims ‘information’ as an inadequate domain and ‘implement tech to learning’ as the adequate domain in each level of digital literacy. Further research is needed to examine effectiveness of project-based learning, problem-based learning, and case study in enhancing digital literacy through qualitative and quantitative research.